Systembetreuung im schulischen Digitalisierungsprozess Mehr Verwaltung als Gestaltung? - Graßmann, Stephan (Young Academics: Soziologie, 2023)
How is digitalisation being implemented in schools? The crucial factor in this respect is the work of system administrators, who play a decisive role in its shaping and realisation as the driving forces behind it. While their interface function provides system administrators unique know-how and expert knowledge, they are, at the same time, structurally limited in their scope of action. This constellation ultimately affects the quality of the implementation of digitalisation in schools. In this study, digitalisation researcher and sociologist Stephan Graßmann analyses the everyday work of system administrators and provides important insights into and ideas on improving digitalisation processes in schools. Honoured with the BDS Award of the Berufsverband Deutscher Soziologinnen und Soziologen e.V. 2023.